Membendung Perbedaan Hari Raya Idul Fitri 1444 H antara BRIN dan Muhammadiyah: Tinjuan al-Qur’an sebagai Konsep Dakwah Berbasis Moderasi Beragama yang Harmoni - Mohammad Jailani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The Qur'an was revealed as a rahmatan lil alamin (mercy to all creations) and a guide for harmonious living. Muslims believe it to be a holy scripture revealed to Prophet Muhammad to establish peace and harmony. However, in the modern era, this ideal often contrasts with reality, as seen in the case of differing determinations of the 1444 AH Eid al-Fitr celebration, which sparked social conflict. This study aims to analyze the role of the Qur'an as an instrument of harmonization from the perspective of religious moderation. The research employs a qualitative case study approach, focusing on the conflict in Bantul, Yogyakarta. Data collection techniques include interviews, observations, and documentation, while data analysis involves reduction, presentation, and verification. The findings indicate a decline in values such as tolerance, empathy, and harmony among Muslims, driven by social jealousy and a lack of understanding of religious moderation. As a solution, this study recommends that the National Research and Innovation Agency (BRIN) support research aligned with the Ministry of Religious Affairs' policies on religious moderation and emphasizes the importance of implementing these values to shape Muslims as ummatan wasatan (a middle and just nation).